Factors Related of Diabetes Mellitus Type II in Kebon Jeruk District (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Diabetes mellitus is a condition that increases blood sugar levels that are chronic as a result of a disruption of body metabolisms such as fat, carbohydrate, and protein due to a deficiency of the hormone insulin. The main problem in people with DM is the occurrence of complications, especially the complications of chronic DM, which is the main cause of morbidity and mortality in DM patients. This study aims to analyze relationship between family history, age, gender, physical activity, obesity, hypertension to the incidence of Diabetes Mellitus type II. This research is a quantitative research type and uses a cross-sectional design. This research was conducted at the Kebon Jeruk District Health Center in West Jakarta in 2018, with a sample size of 77 samples or respondents. Independent variables included family history, age, gender, physical activity, obesity, and hypertension. The dependent variable is type II diabetes mellitus. Analysis of the relationship between the two variables was measured using the chi-square test. The results showed an association between life history, age, physical activity, and obesity with the incidence of type II DM in Kebon Jeruk District Health Center in 2018. It is recommended that people who have a family history of DM to immediately detect DM disease and apply a healthy lifestyle, carry out physical activities for at least 15-20 minutes every day, health workers are also advised to continue to conduct health education related to DM disease.